A new correlation for single and two-phase flow pressure drop in round tubes with twisted-tape inserts - Kanizawa,Fabio T. (2011)
Twisted-tape inserts are frequently used in heat exchangers as a passive and inexpensive heat transfer enhancement method. However, their use results not only heat transfer coefficient increments, but also pressure drop penalties. The present study analyses the literature on single and two-phase frictional pressure drop inside tubes with twisted-tape inserts focusing on the physical mechanism and the effects of the use of twisted-tape in comparison to plain tubes. Experimental data were gathered from the open literature and compared against the available correlations developed in order to predict two-phase frictional pressure drop in tubes containing twisted-tape inserts. It was found that none of the correlations was able to predict such a database accurately. A new correlation to estimate the friction factor for two-phase flows inside tubes with twisted-tape is also proposed. Contrarily to previous studies, the proposed correlation presents reasonable predictions under single and two-phase flow conditions and obeys the trends when the twisted-tape ratio tends to zero and infinite.